Research and thinking on the application of agricultural Internet of things from the perspective of communication operators - Da LUO; Xiaohui FAN; Chang SHU; Yuting SHU (物联网学报)
Agricultural Internet of things (IoT) is an important area of IoT applications,and it is also one of the important application scenarios for telecommunication operators to accelerate the cultivation of emerging services.The current situation and development trend of agricultural in China were summarized in the proposed scheme,and the main business areas and research focus of intelligent application were analyzed.The portrait of the telecommunication operators was analyzed,and the main work of the major operators in expanding smart agriculture was summarized.Finally,the ways of communication operators were explored to cut into the agricultural field.